Can Financial Literacy and Digital Innovation Enhance The Performance and Sustainability of SMEs in Indonesia? - Maslichah Maslichah; Sudarmiatin Sudarmiatin; Agus Hermawan (Cita Konsultindo Research Center, 2023)
This investigation seeks to ascertain the impact of financial literacy and digital innovation on business performance and SME business sustainability in Malang City using quantitative methods, primary data sources, and data collection with the questionnaire method. Path Analysis analyzed data. The results show that financial literacy and Digital innovation positively affect business sustainability and SMEs Performance. The SME business performance does not mediate the effect of digital innovation on SME business sustainability. In contrast, the SME performance variable can mediate the effect of financial literacy on SME business continuity.